Teoria da compreensão da ação de Von Wright e a relação de causalidade no direito penal - Gallinati, Raquel Kobashi (2007)
Deontic Logic to arise in the middle of the 1926, though the thinker Ernest Mally. Years latter, in 1951, George Henrik VON WRIGHT published the article Deontic Logic, stimulating its development. Our goal, on this work, is to show the purposes and convictions of the Deontic Logic of VON WRIGHT and the connection between Finalistic Theory of HANS WELZEL. First of all, we will begin the work, dealing with logic. We will do a brief introduction about logic, with the intention of the enter studies of the Deontic Logic of VON WRIGHT. We will accept yours concepts and theories about the Deontic Logic. This work finish with the connection between causality bordered of the Action Theory of HANS WELZEL and the causality of VON WRIGHT.